New Attack Tricks Antivirus Software. - Heyman, Karen (Computer (00189162), 2007)
The article reports on a new type of computer virus that spreads malicious code in the Web 2.0 environment, tricking the pattern-matching defense employed by common anti-virus software. Web 2.0 is characterized by Web sites that encourage users to add content, and hackers use it after luring victims to infectious sites they set up. The new type of malicious software, or malware, is called dynamic code obfuscation and takes advantage of vulnerabilities in browsers by cloaking JavaScript exploits with polymorphism and obfuscation. The article mentions security vendor Finjan, the Burton Group, Symantec, and the CERT Coordination Center. INSET: DCO and Web 2.0.